2005
DOI: 10.1021/ie050614i
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Strategies for Tocopherols Enrichment Using a Molecular Distillation Process

Abstract: The objective of this study is to compare two different strategies for enriching tocopherols in soybean oil deodorizer distillate (SODD) using a molecular distillation process. The first strategy is to submit crude SODD to a sequence of molecular distillations using different temperatures without any preparation of the raw material. The second strategy is to modify chemically the raw material and submit it to a sequence of distillations. In SODD chemical modification, acylglycerol species are converted into fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 17 publications
0
39
0
2
Order By: Relevance
“…After silylation, the components were separated by GC with mass spectrometry MS for final identification. The compounds separated were tocopherols, sterols, fatty acids and glycerol esters 1 30 33 , enzymatic reaction 34 and molecular distillation 35,36 .…”
Section: Analytical Techniques Used For the Characterization Of Deodomentioning
confidence: 99%
“…After silylation, the components were separated by GC with mass spectrometry MS for final identification. The compounds separated were tocopherols, sterols, fatty acids and glycerol esters 1 30 33 , enzymatic reaction 34 and molecular distillation 35,36 .…”
Section: Analytical Techniques Used For the Characterization Of Deodomentioning
confidence: 99%
“…Para esta reação o diazometano é o mais utilizado, realizando metilação direta. 23 Devido à carência do diazometano, o reagente (trimetilsilil) diazometano (TMSD), solução 2 mol L -1 em hexano da Sigma Aldrich (St. Louis, MO, USA), também foi utilizado e as condições de reação foram estabelecida de acordo com Migowska et al 24 Para esta reação adicionou-se 2 mL de uma solução de 10% de metanol em acetona para aproximadamente 10 mg das amostras em frascos de vidros. As amostras foram homogeneizadas e em seguida adicionou-se 50 µL de TMSD utilizando uma microsseringa.…”
Section: Identificação De Terpenosunclassified
“…They succeeded in removing 96.16% FFAs and recovering 81.23% tocopherols. Martins and coworkers (Martins et al, 2005) reported the isolation of tocopherols by first converting acylglycerols in SODD into FFAs through saponification at 65 ºC followed by acidulation, and then submitting the unsaponifiable product to five stages of molecular distillation. They succeeded in enriching tocopherols (34.14% purity) by 5.8 times.…”
Section: Molecular Distillationmentioning
confidence: 99%